Transcriptomic characterization of the histopathological growth patterns in breast cancer liver metastases - Sophia Leduc; Ha-Linh Nguyen; François Richard; Gitte Zels; Amena Mahdami; Maxim De Schepper; Marion Maetens; Anirudh Pabba; Joris Jaekers; Emily Latacz; Ali Bohlok; Evy Vanderheyden; et al. (Clinical & Experimental Metastasis, 2024)
Metastatic breast cancer (mBC) remains incurable and liver metastases (LM) are observed in approximately 50% of all patients with mBC. In some cases, surgical resection of breast cancer liver metastases (BCLM) is associated with prolonged survival. However, there are currently no validated marker to identify these patients. The interactions between the metastatic cancer cells and the liver microenvironment result in two main histopathological growth patterns (HGP): replacement (r-HGP), characterized by a direct contact between the cancer cells and the hepatocytes, and desmoplastic (d-HGP), in which a fibrous rim surrounds the tumor cells. In patients who underwent resection of BCLM, the r-HGP is associated with a worse postoperative prognosis than the d-HGP. Here, we aim at unraveling the biological differences between these HGP within ten patients presenting both HGP within the same metastasis. The transcriptomic analyses reveal overexpression of genes involved in cell cycle, DNA repair, vessel co-option and cell motility in r-HGP while angiogenesis, wound healing, and several immune processes were found overexpressed in d-HGP LM. Understanding the biology of the LM could open avenues to refine treatment of BC patients with LM.